Avaliação dos impactos da geração fotovoltaica conectada à rede elétrica no âmbito da qualidade da energia : estudo de caso - Dantas, Ozlean de Lima (2019)
Photovoltaic energy has been gaining more and more space in Brazil. This is due to a regulatory energy policy initiated in 2012, distributed generation, worldwide expansion of this technology, reduction of equipment prices and the high potential of solar irradiation available in the country. This work deals with the impacts of the photovoltaic generation connected to the electric grid in the scope of the electric energy quality. The study consisted of a theoretical evaluation and study of a 45kWp microvoltage photovoltaic plant connected to the grid, located in the city of Cuiabá-MT, Brazil. Measurements were made with an electric energy meter and a recorder of quality of the electric energy in several points of the consumer unit equipped with a photovoltaic plant. The measurement methodology followed the criteria defined in Module 8 of the Distribution Procedure (PRODIST) of the National Electric Energy Agency (ANEEL), which deals with the quality of electric energy. The data were evaluated, discussed and compared with the limits established by ANEEL's PRODIST Module 8 and the Brazilian technical standard NBR 16149: 2013, which deals with the connection of photovoltaic systems to the distribution network. The results showed that the consumer unit with the photovoltaic power plant connected to the grid presented steady state voltage values outside the normal range, as established in ANEEL Module 8. The total harmonic distortion of current measured at the output of the inverters, with the plant operating, reached the limits established by NBR16149: 2013, with generation from 26% of nominal power.